Produksi konsentrat karetenoid dari fraksi cair minyak menggunakan metode kromotografi - Nur Wulandari (Institut Pertanian Bogor, 2007)
This research was aimed to obtain an optimum conditions for production of liquid fraction of crude palm (CPO) containing high concentration of carotenoids,as well as to get the optimum condition on production o carotenoids concentrate, by using adsorption column chromatography method at laboratory scale. Adsorbent used were rice hull ash and silica gel. In order to get high amount of carotenoids on liquid fraction of palm o the palm oil was treated with n-hexane and was mixed by using shaker. Based on recovery and tot carotenoids parameters contained in the liquid fraction, the optimum condition to get high total carotenoids o liquid fraction was shown when employing 50% hexane,mixing at 200 rpm for 10 minutes,and decanting for days at ambient temperatures. The palm oil liquid fraction contained 275 ppm carotenoids with 81.0 recovery. The next step was the separation of carotenoids from other components of palm oil by usin adsorption column chromatography method with rice hull ash and silica gel as adsorbents. The optimu condition on separation were found by using ratio of rice hull ash:silica gel 30:10, which produced total corotenoids of 317.2 11g and recovery of carotenoids of 41.7%. The final concentration in carotenoi concentrate was 1865.9 ppm,4 times higher than the initial concentration in CPO. Key words: carotenoids,palm oil,adsorption column hromatography